Positive electrode active material for rechargeable lithium battery, positive electrode including the same, and rechargeable lithium battery including the positive electrode
By using positive electrode active materials composed of olivine, spinel and layered structure particles, the problems of low energy density and voltage efficiency of rechargeable lithium batteries are solved, and high energy density and high efficiency battery performance are achieved.
Patent Information
- Application Number
- CN202510515401.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-24
- Filing Date
- 2025-04-23
- Publication Date
- 2025-10-24
AI Technical Summary
The energy density and average voltage of existing rechargeable lithium batteries are low, making it difficult to meet the requirements of high energy density and high efficiency.
A positive electrode active material composed of olivine structure particles represented by Chemical Formula 1, spinel structure particles represented by Chemical Formula 2, and layered structure particles represented by Chemical Formula 3 is used in combination with a conductive material and a binder to form a high-efficiency positive electrode active material layer.
The energy density and voltage efficiency of rechargeable lithium batteries are improved, achieving economical and efficient battery performance.
Smart Images

Figure CN120834167A_ABST
Abstract
Description
[0001] Cross Reference to Related Applications
[0002] This application claims priority to Korean Patent Application No. 10-2024-0054509, filed on April 24, 2024, the entire contents of which are incorporated herein by reference. TECHNICAL FIELD
[0003] The present disclosure relates herein to a positive electrode active material for a rechargeable lithium battery, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. More particularly, to a positive electrode active material including an olivine-type lithium compound, a positive electrode including the positive electrode active material, and a rechargeable lithium battery including the positive electrode. BACKGROUND
[0004] With the rapid spread of devices using batteries, such as mobile phones, laptop computers, electric vehicles, etc., the demand for rechargeable lithium batteries having high energy density and high capacity is rapidly increasing. Accordingly, research and development to improve the performance of rechargeable lithium batteries are being conducted.
[0005] A rechargeable lithium battery is a battery including a positive electrode and a negative electrode (the positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions) and an electrolyte. When lithium ions are intercalated into and deintercalated from the positive electrode and the negative electrode, the rechargeable lithium battery generates electric energy through oxidation and reduction reactions. SUMMARY
[0006] The present disclosure provides a positive electrode active material that is economical and has high energy density and high average voltage.
[0007] The present disclosure also provides a rechargeable lithium battery that is economical and has high energy density and high efficiency.
[0008] According to an embodiment of the present disclosure, the positive electrode active material can include first particles, second particles, and third particles, the first particles including a compound represented by Chemical Formula 1 and having an olivine structure, the second particles including a compound represented by Chemical Formula 2 and having a spinel structure, and the third particles including a compound represented by Chemical Formula 3 and having a layered structure. The first particles and the second particles can constitute a main active material, the amount of the main active material can be about 80 parts by weight to about 90 parts by weight based on 100 parts by weight of the positive electrode active material, and the amount of the third particles can be about 10 parts by weight to about 20 parts by weight based on 100 parts by weight of the positive electrode active material.
[0009] Chemical Formula 1:
[0010] Li a1 Fe x1 B y1PO 4-b1
[0011] In Chemical Formula 1, 0.8≤a1≤1.2, 0.1≤x1≤1.0, 0.001≤y1≤0.05, 0≤b1≤0.05, x1+y1=1, and B is at least one of Ti, Mg, V, and Nb.
[0012] Chemical Formula 2:
[0013] Li a2 Mn x2 Mg y2 O 4-b2
[0014] In Chemical Formula 2, 0.8≤a2≤1.2, 1.9≤x2≤2.05, 0≤y2≤0.05, and 0≤b2≤0.05.
[0015] Chemical Formula 3:
[0016] Li a3 Ni x3 Co y3 E z3 O 2-b3
[0017] In Chemical Formula 3, 0.8≤a2≤1.2, 0.9≤x3≤1.0, 0≤y3≤0.1, 0≤z3≤0.1, 0≤b3≤0.05, x3+y3+z3=1, and E can be Al and / or Mn.
[0018] According to another embodiment of the present disclosure, a positive electrode for a rechargeable lithium battery can include a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector. The positive electrode active material layer can include a positive electrode active material, a conductive material, and a binder.
[0019] According to another embodiment of the present disclosure, a rechargeable lithium battery can include a positive electrode, a negative electrode including a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector, and a separator between the positive electrode and the negative electrode. BRIEF DESCRIPTION OF DRAWINGS
[0020] The accompanying drawings are included to provide a further understanding of the present disclosure, and are incorporated in and constitute a part of this specification. The drawings illustrate the embodiments of the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0021] Figure 1 A simplified conceptual diagram of a rechargeable lithium battery according to some embodiments of the present disclosure is shown.
[0022] Figures 2 to 5FIG. 1 is a schematic view showing a rechargeable lithium battery according to some embodiments.
[0023] Figure 6 and Figure 7 FIG. 2 is a magnified view showing a positive electrode active material layer of a rechargeable lithium battery according to some embodiments of the present disclosure.
[0024] Figure 8A and Figure 8B FIG. 3 is a scanning electron microscope (SEM) image showing a positive electrode active material of Preparation Example 1 of the present disclosure.
[0025] Figure 8C and Figure 8D FIG. 4 is a scanning electron microscope (SEM) image showing a positive electrode active material of Preparation Example 2 of the present disclosure.
[0026] Figure 9A and Figure 9B FIG. 5 is a scanning electron microscope (SEM) image showing a positive electrode active material of Preparation Example 3 of the present disclosure.
[0027] Figure 10A and Figure 10B FIG. 6 is a scanning electron microscope (SEM) image showing a positive electrode active material of Preparation Example 4 of the present disclosure. DETAILED DESCRIPTION
[0028] In order to fully understand the layout and effects of the present disclosure, embodiments of the present disclosure will be described in greater detail with reference to the accompanying drawings. However, the present disclosure can be embodied in one or more suitable forms, and should not be construed as being limited to one or more embodiments set forth herein, and one or more appropriate changes and modifications can be made. The embodiments are provided so that the present disclosure will be thorough and complete, and will fully convey the scope of the present disclosure to those skilled in the art to which the present disclosure pertains.
[0029] In this specification, it will be understood that when an element is referred to as being "on" another element, it can be directly on the other element, or intervening elements can be present therebetween. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements present therebetween.
[0030] In the drawings, the size (e.g., thickness) of components is exaggerated for clarity and ease of explanation of the technical content. Throughout the specification, the same reference numerals and / or symbols refer to the same elements, and repeated description thereof can not be provided.
[0031] The singular form "a," "an," and "the" include plural references unless the context clearly dictates otherwise. Additionally, the phrase "A or B" can mean "A but not B", "B but not A", or "A and B" unless expressly stated otherwise. The term "comprises the comprises / includes" and / or "comprising / including" used in this specification does not exclude the presence of one or more other components.
[0032] In this specification, "combination thereof" can refer to a mixture, a stack, a composite, a copolymer, an alloy, a blend, and / or a reaction product of components.
[0033] Unless otherwise defined in this specification, the particle diameter can be an average particle diameter (average diameter or average size). Also, the particle diameter refers to an average particle diameter (D 50 ), which refers to the diameter of particles whose cumulative volume is about 50 vol% in the particle size distribution. The average particle diameter (D 50 ) can be measured by any appropriate method, for example, can be measured by a particle size analyzer, or can be measured using a transmission electron microscope (TEM) image and / or a scanning electron microscope (SEM) image. In one or more embodiments, the average particle diameter is measured by using a measuring device using dynamic light scattering, in which data analysis is performed to count the number of particles for each particle size range, and then the average particle diameter (D 50 ) value can be obtained by calculation therefrom. Also, the average particle diameter can be measured using a laser diffraction method. When measured by the laser diffraction method, after dispersing the particles to be measured in a dispersion medium, the dispersion medium is introduced into a commercial laser diffraction particle size measuring instrument (for example, Micro-Trak MT-3000 TM ), and is irradiated with ultrasonic waves of about 28 kHz at an output of about 60 W, and then the average particle diameter (D 50 ) based on the particle size distribution of about 50% in the measuring instrument can be calculated. In this specification, when the particles are spherical, "diameter" or "size" indicates the particle diameter, and when the particles are non-spherical, "diameter" or "size" indicates the length of the long axis.
[0034] It will be understood that, although the terms first, second, etc. can be used herein to describe various elements, these elements should not be limited by these terms. These terms are only used to distinguish one element from another. Thus, a first element could be termed a second element without departing from the teachings of the present application. Similarly, a second element could be termed a first element.
[0035] As used herein, the terms "use," "using," and "used" can be taken in their broadest possible context as synonymous with the terms "utilize," "utilizing," and "utilized," respectively.
[0036] As used herein, the expressions such as "at least one of," "one of," and "selected from the group of," when preceding the list of elements, modify the entire list of elements and do not modify the individual elements of the list. For example, "at least one of a, b, and c," "one of a, b, and c," and "a, b, and / or c" can indicate only a, only b, only c, both a and b, both a and c, both b and c, all of a, b, and c, or variations thereof.
[0037] Further, as the embodiments of the disclosure are described, the use of "may" indicates that "one or more embodiments of the disclosure."
[0038] Spatially relative terms (such as "beneath", "below", "lower", "above", "upper", "bottom", "top", and the like) can be used herein for ease of description to describe one element's or feature's relationship to another element(s) or feature(s) as illustrated in the figures. It will be understood that the spatially relative terms are intended to encompass different orientations of the device in use or operation in addition to the orientations depicted in the figures. For example, if a device in the figures is turned over, elements described as "below" or "beneath" other elements or features would then be oriented "above" or "over" the other elements or features. Thus, the term "below" can encompass both an orientation of above and below. The device can be otherwise oriented (rotated 90 degrees or at other orientations) and the spatially relative descriptors used herein interpreted accordingly. Well-known functions or constructions can not be described in detail for brevity.
[0039] As used herein, the terms "substantially", "approximately", and like terms are used as terms of approximation and not as terms of degree, and are intended to account for the inherent deviations in a measuring or computing process. As used herein, "about" or "approximately" includes recited values and means an acceptable range of deviation of a particular value that would be determined by one of ordinary skill in the art considering measurements and the error in measurement associated with a particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the recited value.
[0040] Any numerical range recited herein is intended to include all sub-ranges of the same entire number of increments within the recited range. For example, a range of "1.0 to 10.0" is intended to include all sub-ranges, for example, 2.4 to 7.6, within the same entire number of 10 increments, for example, 1.0, 1.6, 2.4, 2.5, 3.4, 3.5, 4.2, 5.1, 6.3, 6.4, 7.2, 7.6, 8.4, 9.1, 9.2, 9.6, and 10.0. Any maximum numerical limitation recited herein is intended to include all lower numerical limitations subsumed therein and any minimum numerical limitation recited in this specification is intended to include all higher numerical limitations subsumed therein. Accordingly, the applicant reserves the right to amend this specification, including the claims, to expressly recite any sub-range subsumed within the ranges expressly recited in this specification.
[0041] In view of the overall disclosure, those of ordinary skill in the art will recognize that each appropriate feature of the various embodiments of the present disclosure can be combined, in part or in whole, with each other, and can be technically interlocked and operated in various appropriate ways, and unless otherwise stated or implied, each embodiment can be implemented independently of each other or in combination with each other in any appropriate manner.
[0042] Figure 1 To illustrate a simplified conceptual diagram of a rechargeable lithium battery according to one or more embodiments of the present disclosure. Reference is made to Figure 1 The rechargeable lithium battery can include a positive electrode 10, a negative electrode 20, a separator 30, and an electrolyte ELL.
[0043] The positive electrode 10 and the negative electrode 20 can be spaced and / or separated from each other (e.g., spaced apart and / or divided), and the separator 30 is between the two. The separator 30 can be disposed between the positive electrode 10 and the negative electrode 20. The positive electrode 10, the negative electrode 20, and the separator 30 can be in contact with the electrolyte ELL. The positive electrode 10, the negative electrode 20, and the separator 30 can be impregnated with the electrolyte ELL.
[0044] The electrolyte ELL can be a medium for transporting lithium ions between the positive electrode 10 and the negative electrode 20. In the electrolyte ELL, lithium ions can move toward the positive electrode 10 or the negative electrode 20 through the separator 30.
[0045] The positive electrode 10
[0046] The positive electrode 10 for the rechargeable lithium battery can include a positive electrode current collector COL1 and a positive electrode active material layer AML1 formed on the positive electrode current collector COL1. The positive electrode active material layer AML1 can include a positive electrode active material, and can further include a binder and / or a conductive material. Reference will be made to Figure 6 and Figure 7The positive electrode active material layer AML1 according to one or more embodiments of the present disclosure is described in more detail. An aluminum (Al) foil can be used as the positive electrode current collector COL1, but the present disclosure is not limited thereto.
[0047] Negative electrode 20
[0048] The negative electrode 20 for the rechargeable lithium battery can include a negative electrode current collector COL2 and a negative electrode active material layer AML2 on the negative electrode current collector COL2. The negative electrode active material layer AML2 can include a negative electrode active material, and can further include a binder and / or an electrically conductive material (e.g., an electrically conductive material).
[0049] The negative electrode active material layer AML2 can include, for example, about 90 wt% to about 99.5 wt% of the negative electrode active material, about 0.5 wt% to about 5 wt% of the binder, and about 0 wt% to about 5 wt% of the electrically conductive material.
[0050] The binder can be used to adhere the negative electrode active material particles to each other, and also to adhere the negative electrode active material to the negative electrode current collector COL2. The binder can include a non-aqueous binder, an aqueous binder, a dry binder, and / or a combination (e.g., any suitable combination) thereof.
[0051] The non-aqueous binder can include polyvinyl chloride, carboxylated polyvinyl chloride, polyfluoroethylene, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide imide, polyimide, and / or a combination (e.g., any suitable combination) thereof.
[0052] The aqueous binder can be selected from styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluoro rubber, polyethylene oxide, polyvinylpyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol, and / or a combination (e.g., any suitable combination) thereof.
[0053] When the aqueous binder is used as the binder in the negative electrode active material layer AML2, a cellulose-based compound capable of imparting viscosity can be further included. The cellulose-based compound can include at least one of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, and alkali metal salts thereof. The alkali metal can include Na, K, and / or Li.
[0054] The dry binder can be a polymeric material capable of fibrillation. For example, the dry binder can be polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, and / or combinations thereof (e.g., any suitable combination).
[0055] The electrically conductive material can be used to impart electrical conductivity (e.g., electronic conductivity) to the electrode. Any material that does not cause chemical changes (e.g., does not cause undesirable chemical changes in a rechargeable lithium battery) and conducts electrons can be used in the battery. Non-limiting examples of electrically conductive materials include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fibers, carbon nanofibers, and carbon nanotubes; metal-based materials including copper, nickel, aluminum, silver, and the like in the form of a metal powder and / or a metal fiber; electrically conductive polymers such as polyphenylene derivatives; and / or mixtures thereof (e.g., any suitable mixture).
[0056] The negative electrode current collector COL2 can include a copper foil, a nickel foil, a stainless steel foil, a titanium foil, a nickel foam, a copper foam, a polymer substrate coated with an electrically conductive metal, and / or combinations thereof (e.g., any suitable combination).
[0057] The negative electrode active material
[0058] The negative electrode active material can include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.
[0059] The material that reversibly intercalates / deintercalates lithium ions can include a carbon-based negative electrode active material such as, for example, crystalline carbon, amorphous carbon, and / or combinations thereof (e.g., any suitable combination). The crystalline carbon can be graphite such as amorphous (e.g., randomly shaped), flaky, sheet-like, spherical, and / or fibrous natural graphite and / or artificial graphite. The amorphous carbon can be soft carbon, hard carbon, meso-phase pitch carbonization products, calcined coke, and the like.
[0060] The lithium metal alloy includes an alloy of lithium with a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0061] The material capable of doping / dedoping lithium can be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material can include silicon, a silicon-carbon composite, SiO x (0 < x < 2), a Si-Q alloy (where Q is selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements (excluding Si), Group 15 elements, Group 16 elements, transition metals, rare earth elements, and / or combinations thereof (e.g., any suitable combination)). The Sn-based negative electrode active material can include Sn, SnO y(0 < y < 2) (e.g., SnO2), Sn-based alloys, and / or combinations (e.g., any suitable combination) thereof.
[0062] The silicon-carbon composite can be a composite of silicon and amorphous carbon. According to one or more embodiments, the silicon-carbon composite can be in the form of silicon particles and amorphous carbon coated on the surface of the silicon particles. For example, the silicon-carbon composite can include secondary particles (nuclei) in which primary silicon particles are assembled (aggregated) and an amorphous carbon coating (shell) on the surface of the secondary particles. The amorphous carbon can also be between the primary silicon particles, for example, the primary silicon particles can be coated with amorphous carbon. The secondary particles can be dispersed in an amorphous carbon matrix.
[0063] The silicon-carbon composite can further include crystalline carbon. For example, the silicon-carbon composite can include a core including crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core.
[0064] The Si-based negative electrode active material and / or the Sn-based negative electrode active material can be used in combination with a carbon-based negative electrode active material.
[0065] Separator 30
[0066] According to the type (kind) of the rechargeable lithium battery, the separator 30 can be present between the positive electrode 10 and the negative electrode 20. The separator 30 can include a polyethylene separator, a polypropylene separator, a polyvinylidene fluoride separator, or a multi-layer film of two or more layers thereof (a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polyethylene / polypropylene three-layer separator, etc.).
[0067] The separator 30 can include a porous substrate and a coating layer on the surface (e.g., one or both (e.g., simultaneously) surfaces (e.g., opposite surfaces)) of the porous substrate, the coating layer including an organic material, an inorganic material, and / or a combination (e.g., any suitable combination) thereof.
[0068] The porous substrate can be a polymer film formed of any one polymer selected from the group consisting of a polyolefin (such as polyethylene and / or polypropylene), a polyester (such as polyethylene terephthalate and / or polybutylene terephthalate), a polyacetal, a polyamide, a polyimide, a polycarbonate, a polyether ketone, a polyarylether ketone, a polyetherimide, a polyamideimide, a polybenzimidazole, a polyether sulfone, a polyphenylene ether, a cyclic olefin copolymer, a polyphenylene sulfide, a polyethylene naphthalate, glass fiber, and polytetrafluoroethylene and / or can be a copolymer and / or a mixture of two or more thereof.
[0069] The organic material can include a polyvinylidene fluoride-based polymer and / or a (meth)acrylic-based polymer.
[0070] The inorganic material can include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and / or combinations thereof (e.g., any suitable combination). However, the present disclosure is not limited to these examples.
[0071] The organic material and the inorganic material can be mixed in one coating layer, or a coating layer including the organic material and a coating layer including the inorganic material can be stacked.
[0072] Electrolyte ELL
[0073] The electrolyte ELL for the rechargeable lithium battery can include a non-aqueous organic solvent and a lithium salt.
[0074] The non-aqueous organic solvent can be used as a medium for transporting ions participating in an electrochemical reaction of the battery.
[0075] The non-aqueous organic solvent can include a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent, an aprotic solvent, and / or combinations thereof (e.g., any suitable combination).
[0076] The carbonate-based solvent can include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), etc.
[0077] The ester-based solvent can include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanolide, mevalonolactone, valerolactone, caprolactone, etc.
[0078] The ether-based solvent can include dibutyl ether, tetraglyme, diglyme, glyme, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc. In addition, the ketone-based solvent can include cyclohexanone, etc. The alcohol-based solvent can include ethanol, isopropyl alcohol, etc., and the aprotic solvent can include: nitriles such as R-CN (wherein R is a C2 to C20 linear, branched, or cyclic hydrocarbon group, and further includes a double bond, an aromatic ring, or an ether bond, etc.); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolanes, etc.
[0079] The non-aqueous organic solvent can be used alone or in a combination of two or more.
[0080] In addition, when the carbonate-based solvent is used, a cyclic carbonate and a chain carbonate can be mixed and used, and the cyclic carbonate and the chain carbonate can be mixed in a volume ratio of about 1:1 to about 1:9.
[0081] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, ensures the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) (wherein x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluoro(oxalato)borate (LiDFOB), lithium difluorobis(oxalato)phosphate (LiDFBOP) and lithium bis(oxalato)borate (LiBOB).
[0082] Rechargeable lithium battery
[0083] Rechargeable lithium batteries may be classified according to their shapes into cylindrical, prismatic, pouch-type, or coin-type (kinds) batteries, etc. Figures 2 to 5 A schematic diagram illustrating a rechargeable lithium battery according to an embodiment. Figure 2 A cylindrical battery is shown, Figure 3 A prismatic cell is shown, and Figure 4 and Figure 5 Shows a pouch type battery. Figures 2 to 5 , the rechargeable lithium battery 100 may include an electrode assembly 40 and a case 50 including the electrode assembly 40 therein, the electrode assembly 40 including a separator 30 between a positive electrode 10 and a negative electrode 20. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte. Figure 2 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 3 As shown in , the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 4 and Figure 5 As shown in , the rechargeable lithium battery 100 may include electrode tabs 70, which may be, for example, a positive electrode tab 71 and a negative electrode tab 72, serving as an electrical path for guiding current generated in the electrode assembly 40 to the outside of the battery.
[0084] A rechargeable lithium battery according to one or more embodiments may be applied to automobiles, mobile phones, and / or one or more appropriate types (kinds) of electronic devices, as non-limiting examples.
[0085] Figure 6 and Figure 7 is a magnified view of a positive electrode active material layer of a rechargeable lithium battery according to some embodiments of the present disclosure. Referring to Figure 6 and Figure 7 , the positive electrode active material layer AML1 (see Figure 1 ) can include first particles PTC1, second particles PTC2, third particles PTC3, a conductive material CDM, and a binder BND. The plurality of first particles PTC1, the plurality of second particles PTC2, and the plurality of third particles PTC3 can constitute a positive electrode active material according to some embodiments of the present disclosure.
[0086] The positive electrode active material layer AML1 can further include a component serving as a sacrificial positive electrode.
[0087] The amount of the positive electrode active material particles (the first particles PTC1, the second particles PTC2, and the third particles PTC3) in the positive electrode active material layer AML1 can be in the range of about 90 wt% to about 99 wt% with respect to 100 wt% of the positive electrode active material layer AML1. Each of the amounts of the binder BND and the conductive material CDM can be about 0.5 wt% to about 5 wt% with respect to 100 wt% of the positive electrode active material layer AML1.
[0088] The binder BND can bind the first particles PTC1, the second particles PTC2, the third particles PTC3, and the conductive material CDM to each other. For example, the binder BND can include at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, an oxirane-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon, but the present disclosure is not limited to these examples.
[0089] The conductive material CDM can serve to improve the electrical conductivity of the positive electrode active material layer AML1. Any conductive material that does not cause a chemical change in the positive electrode active material layer AML1 can be used. For example, the conductive material CDM can include: carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon nanofibers, and carbon nanotubes; metal-based materials containing copper, nickel, aluminum, silver, etc. and having a form of metal powder or metal fiber; conductive polymers such as polyphenylene derivatives; or a mixture thereof.
[0090] Hereinafter, each of the first particles PTC1, the second particles PTC2, and the third particles PTC3 will be explained in more detail.
[0091] First particles
[0092] The first particles PTC1 can include a lithium compound having an olivine structure represented by Chemical Formula 1:
[0093] Chemical Formula 1
[0094] Li a1 Fe x1 B y1 PO 4-b1
[0095] In Chemical Formula 1, 0.8≤a1≤1.2, 0.1≤x1≤1.0, 0.001≤y1≤0.05, 0≤b1≤0.05, and x1+y1=1 can be satisfied. B can be at least one of Ti, Mg, V, and Nb and can be a dopant doped in the first particles PTC1. The dopant B can control the size of the primary particles to be uniform, and thus can improve the charge and discharge efficiency, low-temperature properties, and life characteristics of the rechargeable lithium battery.
[0096] In an embodiment, the first particles PTC1 can include a coating layer on a surface thereof. The coating layer can cover the entire surface of the first particles PTC1 or can cover a portion of the surface of the first particles PTC1. The first particles PTC1 include a coating layer containing a carbon element. The coating layer can include, for example, a carbon element and / or a carbon-containing compound. Due to the coating layer, the first particles PTC1 can have improved structural stability and electrical conductivity.
[0097] The coating layer can further include at least one metal-containing compound among a titanium-containing compound, a magnesium-containing compound, and a vanadium-containing compound. The metal-containing compound (such as the titanium-containing compound, the magnesium-containing compound, and the vanadium-containing compound) can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a synthetic compound thereof, or a mixture thereof. The metal-containing compound can further include other metal or non-metal elements. For example, the metal-containing compound can further include lithium.
[0098] The first particles PTC1 can further include carbon (carbon element) derived from the coating layer. The amount of carbon per one of the first particles PTC1 can be about 0.5 wt% to about 10 wt%, about 1 wt% to about 3 wt%, or about 1.5 wt% to about 2.5 wt%.
[0099] Referring again to Figure 6 , the first particles PTC1 can have a single particle form. In the description, a single particle can mean a separate particle having no grain boundary inside the particle. The single particle has one phase of morphology, and can mean a monolithic structure, a whole structure, or a non-aggregated particle (in which the particle exists as an un-aggregated independent phase). For example, the single particle can be a single crystal. In addition, the single particle can be a particle containing several crystals. The single particle can be in a separate form.
[0100] The first particle PTC1 can be a nano-sized positive electrode active material. The first particle PTC1 can include at least one first primary particle. As used herein, a primary particle can be a single particle as in embodiments in which the first particle or the second particle is provided in a single particle form. A primary particle can also be a particle that is combined to form a secondary particle form, for example, primary particles are aggregated to form a secondary particle. In embodiments, the first particle PTC1 can have a spherical or spheroid shape in which the first primary particles are aggregated. In another embodiment, although the first primary particles are aggregated, the first particle PTC1 can not have a spherical shape, but can have a random shape.
[0101] The first particle PTC1 can be provided in various sizes. For example, the average particle diameter of the first particle PTC1 can be about 500 nm to about 2.5 μm or about 1 μm. The minimum particle diameter of the first particle PTC1 (i.e., the size of the first primary particle, for example, the particle diameter of the smaller first particle PTC1, i.e., the first particle PTC1 whose size corresponds to a single particle of the minimum particle diameter as used herein, refers to the first particle PTC1) can be about 100 nm to about 500 nm or about 200 nm to about 300 nm.
[0102] In embodiments, the average particle diameter can be measured by a particle size analyzer. The average particle diameter (D50) can mean the diameter of a particle whose cumulative volume is about 50 vol% in a particle size distribution. 50 ) can mean the diameter of a particle whose cumulative volume is about 50 vol% in a particle size distribution.
[0103] In embodiments, the minimum particle diameter (i.e., the size of the first primary particle) can mean the diameter measured by randomly selecting about 30 primary particles on an electron microscope image of the first particle PTC1.
[0104] Referring again to Figure 7 , in embodiments, the first particle PTC1 has a polycrystal form, and can include a secondary particle in which two or more first primary particles are aggregated. In other words, one first particle PTC1 can include a plurality of first primary particles that are aggregated with each other, thereby constituting a secondary particle. The first particle PTC1 can have a spherical or spheroid shape.
[0105] In embodiments, the first particle PTC1 can further include a grain boundary coating layer on the surface of each first primary particle. The grain boundary coating layer can be present in the first particle PTC1. The grain boundary coating layer can be formed along the interface between the first primary particles inside the first particle PTC1. In other words, the grain boundary coating layer can mean a layer formed of a material coated on the grain boundaries in the first particle PTC1. The grain boundary coating layer can include elemental carbon and / or a carbon-containing compound. The grain boundary coating layer can further include at least one metal-containing compound among a titanium-containing compound, a magnesium-containing compound, and a vanadium-containing compound.
[0106] The inside of the first particle PTC1 can mean the entire inside of the first particle PTC1 except for the surface of the first particle PTC1. For example, the inside of the first particle PTC1 can mean the entire inside from a depth of about 10 nm of the surface of the first particle PTC1, or a region from a depth of about 10 nm to a depth of about 2 μm.
[0107] Because the first particle PTC1 further includes the grain boundary coating portion (grain boundary coating layer), the structural stability can be enhanced, and a uniform coating layer can be formed on the surface of the first particle PTC1. In addition, because the first particle PTC1 further includes the grain boundary coating portion, the electrical conductivity of the first particle PTC1 can be further improved.
[0108] The first particle PTC1 can further include carbon derived from the coating and / or the grain boundary coating layer. The amount of carbon in the first particle PTC1 can be about 0.5 wt% to about 10 wt%, about 1 wt% to about 3 wt%, or about 1.5 wt% to about 2.5 wt%.
[0109] If the first particle PTC1 is a secondary particle, the average particle diameter of the first particle PTC1 can be about 2 μm to about 15 μm, about 3 μm to about 10 μm, or about 3 μm to about 7 μm. For example, the average particle diameter of the first particle PTC1 can be about 5 μm. In embodiments, the average particle diameter can be measured using a particle size analyzer. The average particle diameter (D 50 ) can mean the diameter of a particle of which the cumulative volume is about 50 vol% in a particle size distribution.
[0110] The average size (diameter) of the first primary particle can be about 200 nm or less. For example, the average size of the first primary particle can be about 10 nm to about 200 nm, about 20 nm to about 200 nm, about 50 nm to about 200 nm, or about 100 nm to about 200 nm. In embodiments, the average particle size (average size) of the first primary particle can mean the diameter measured by randomly selecting about 30 primary particles on an electron microscope image of the positive electrode active material. The size of the first primary particle can be uniform.
[0111] If the first particle PTC1 has a polycrystalline form, the size of the first primary particle can be smaller than in the case where the first particle PTC1 is a single particle form. For example, the size of the first primary particle in the case where the first particle PTC1 is a polycrystalline form can be about 100 nm smaller than the size of the first primary particle in the case where the first particle PTC1 is a single crystal form.
[0112] If the average particle size of the first particles PTC1 and the average size of the first primary particles satisfy the above ranges, and if the size of the first primary particles is uniform, the charge and discharge capacity and the low temperature capacity of the rechargeable lithium battery including the particles can be improved.
[0113] The first particles PTC1 can have a spherical shape in which the first primary particles having a nano size are aggregated. Because the first primary particles are closely aggregated in the first particles PTC1, the particles can have the following properties. The first particles PTC1 can have a spherical or spheroid shape. The average particle size (D50) of the first particles PTC1 can be about 2 μm to about 15 μm. The porosity of the first particles PTC1 can be about 20% to about 40%. The span value of the first particles PTC1 analyzed by a particle size analyzer can be about 0.3 to about 0.75. The porosity (n) can be defined as the pore volume (V p ) divided by the total volume of the particles (V t ), or n = V p / V t . The span value is represented by (D 90 -D 10 ) / D 50 . As used herein, the term "D 10 " refers to the average particle size of the particles when the cumulative percentage reaches 10% by volume in the particle size distribution, and the term "D 90 " refers to the average particle size of the particles when the cumulative percentage reaches 90% by volume in the particle size distribution.
[0114] Second particle
[0115] The second particles PTC2 can include a lithium compound having a spinel structure represented by Chemical Formula 2:
[0116] Chemical Formula 2
[0117] Li a2 Mn x2 Mg y2 O 4-b2
[0118] In Chemical Formula 2, 0.8≤a2≤1.2, 1.9≤x2≤2.05, 0≤y2≤0.05, and 0≤b2≤0.05 can be satisfied. The Mg can be a dopant doped in the second particles PTC2. The Mg can control the size of the primary particles to be uniform, thereby stabilizing the crystal structure of the positive electrode active material, and improving the charge and discharge efficiency, the low temperature property, and the life characteristics of the rechargeable lithium battery. In addition to the Mg, the second particles PTC2 can further include Al as a dopant.
[0119] Referring again to Figure 6 andFigure 7 The second particles PTC2 can have a polycrystalline form, and can include secondary particles in which two or more second primary particles are aggregated. In other words, one second particle PTC2 can include a plurality of second primary particles aggregated with each other. The second particle PTC2 can have an aggregated spherical shape of the second primary particles, and can have a random shape although the second primary particles are aggregated.
[0120] The average particle diameter of the second particles PTC2 can be about 3 μm to about 20 μm, about 4 μm to about 15 μm, or about 5 μm to about 10 μm. For example, the average particle diameter of the second particles PTC2 can be about 8 μm. In embodiments, the average particle diameter can be measured by a particle size analyzer. The average particle diameter (D50) can mean the diameter of particles in which the cumulative volume is about 50 vol% in a particle size distribution. 50 ) can mean the diameter of particles in which the cumulative volume is about 50 vol% in a particle size distribution.
[0121] The average size (diameter) of the second primary particles constituting the second particles PTC2 can be about 3 μm or less. For example, the average particle diameter of the second primary particles can be about 300 nm to about 3 μm, about 500 nm to about 3 μm, about 1 μm to about 3 μm, or about 2 μm to about 3 μm. In embodiments, the average particle size of the second primary particles can mean the diameter measured by randomly selecting about 30 primary particles on an electron microscope image of the positive electrode active material. The size of the second primary particles can be uniform. The first primary particles can have an average size smaller than the average size of the second primary particles. The average size difference between the second primary particles and the first primary particles can be about 300 nm or more.
[0122] The second particles PTC2 can include a second coating layer on the surface of the particles. By including the second coating layer, the second particles PTC2 can effectively suppress structural collapse due to repeated charging and discharging.
[0123] The second coating layer can include a metal-containing compound of a boron-containing compound, an aluminum-containing compound, or a combination of a boron-containing compound and an aluminum-containing compound. The metal-containing compound in each of the second coating layers can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a synthetic compound thereof, or a mixture thereof. The metal-containing compound can further include other metal or non-metal elements. For example, the second coating layer can further include lithium, manganese, and / or nickel.
[0124] Third particle
[0125] The third particles PTC3 can include a lithium compound having a layered structure represented by Chemical Formula 3:
[0126] Chemical Formula 3
[0127] Li a3 Nix3 Co y3 E z3 O 2-b3
[0128] In Chemical Formula 3, 0.8≤a2≤1.2, 0.9≤x3≤1.0, 0≤y3≤0.1, 0≤z3≤0.1, 0≤b3≤0.05, x3+y3+z3=1, and E can be Al and / or Mn.
[0129] The third particles PTC3 can have a single particle form similar to the first particles PTC1. Also, the description of the single particle can be the same as or similar to the above description of the first particles PTC1. The third particles PTC3 can have a form composed of one single type of particles. In another embodiment, the third particles PTC3 can have a form in which a plurality of single particles are attached to each other (i.e., in a secondary particle form). The positive electrode active material according to the present disclosure can include the third particles PTC3 in a single particle form, and high capacity and high energy density of the rechargeable lithium battery including the positive electrode active material can be achieved.
[0130] In an embodiment, the third particles PTC3 can include a third coating layer on a surface thereof. By including the third coating layer, structural collapse due to repeated charging and discharging can be effectively suppressed. Accordingly, the life characteristics of the rechargeable lithium battery can be improved.
[0131] The third coating layer can include a metal-containing compound including a boron-containing compound, an aluminum-containing compound, or a combination of the boron-containing compound and the aluminum-containing compound. The metal-containing compound in the third coating layer can be, for example, a metal oxide, a metal hydroxide, a metal carbonate, a synthetic compound thereof, or a mixture thereof. The metal-containing compound can further include other metal or non-metal elements. For example, the third coating layer can further include lithium, manganese, and / or nickel.
[0132] A method for measuring the metal content in the third coating layer of the third particles PTC3 can include scanning electron microscope-energy dispersive X-ray spectroscopy (SEM-EDS) on the third particles PTC3. Through the analysis, the boron and / or aluminum content in the third coating layer can be confirmed. As a method for measuring the metal content in the third coating layer, in addition to SEM-EDS, inductively coupled plasma-mass spectrometry (ICP-MS), inductively coupled plasma optical emission spectroscopy (ICP-OES), etc. can be used.
[0133] The average particle diameter of the third particles PTC3 can be about 2 μm to about 15 μm, about 2 μm to about 10 μm, or about 2 μm to about 5 μm. The average particle diameter of the third particles PTC3 can be greater than the average particle diameter of the first particles PTC1.
[0134] In an embodiment, the average particle size of the third particles PTC3 can be obtained by determining a particle size (D50) corresponding to a cumulative volume of about 50 vol% in a particle size distribution obtained by laser diffraction analysis. 50 In another embodiment, the average particle size of the third particles PTC3 can be obtained by measuring diameters of about 30 third particles PTC3 randomly selected from an electron microscope image of the positive electrode active material and calculating an arithmetic mean of the measured diameters.
[0135] In another embodiment of the present disclosure, the third particles PTC3 can have a secondary particle form in which a plurality of third primary particles are aggregated. In this case, the third particles PTC3 can have a granular or spherical shape, and the average particle size of the third particles PTC3 can be about 10 μm to about 30 μm, about 10 μm to about 20 μm, or about 10 μm to about 15 μm.
[0136] In another embodiment of the present disclosure, the third particles PTC3 can exist in a mixture type of a compound in a single particle form and a compound in a secondary particle form.
[0137] Referring again to Figure 6 and Figure 7 the positive electrode active material according to an embodiment of the present disclosure will be explained in more detail. The first particles PTC1 and the second particles PTC2 can constitute a main active material, and the amount of the main active material can be about 80 parts by weight to about 90 parts by weight based on 100 parts by weight of the positive electrode active material.
[0138] The lithium iron phosphate-based positive electrode active material (the first particles PTC1) having an olivine crystal structure is relatively inexpensive compared to other positive electrode materials, and has excellent stability and life characteristics. But the positive electrode active material has a low energy density, and it is difficult to use at a high voltage. The lithium manganese oxide-based positive electrode active material (the second particles PTC2) having a spinel structure has a high average voltage and excellent stability, and is inexpensive, but like the positive electrode active material having the first particles PTC1, can have a low energy density.
[0139] Because the first particles PTC1 and the second particles PTC2 are mixed and used as a main active material in the positive electrode active material according to the present disclosure, it is inexpensive and stable, and high average voltage and excellent life characteristics can be achieved. The relatively low energy density can be improved by including the third particles PTC3 having excellent capacity and output characteristics. The rechargeable lithium battery including the positive electrode active material according to an embodiment of the present disclosure can have an energy density of about 450 Wh / kg to about 600 Wh / kg, about 450 Wh / kg to about 550 Wh / kg, or about 470 Wh / kg to about 530 Wh / kg.
[0140] The mixing ratio of the first particles PTC1 and the second particles PTC2 can be about 4:6 to about 6:4 or about 4.5:5.5 to about 5.5:4.5, based on weight. In this case, the amount of Mn in the main active material composed of the first particles PTC1 and the second particles PTC2 can be about 40 mol% to about 70 mol%, about 50 mol% to about 70 mol%, or about 50 mol% to about 60 mol%, based on the metal elements other than lithium in the main active material. The Mn content is similar to the manganese content of a common lithium manganese iron phosphate (hereinafter, referred to as LMFP) positive electrode active material.
[0141] By appropriately mixing and using the first particles PTC1 and the second particles PTC2 such that the above amount of manganese is obtained, a positive electrode active material exhibiting similar electrochemical properties to LMFP but being more easily manufactured and processed than LMFP can be obtained. In the present disclosure, the amount of Mn in the main active material means the molar amount of Mn with respect to the total moles of all metals in the total main active material including the first particles PTC1 and the second particles PTC2, excluding lithium and a small amount of a doping material (e.g., B of Chemical Formula 1 and Mg of Chemical Formula 2).
[0142] The amount of the third particles PTC3 can be about 10 parts by weight to about 20 parts by weight, based on 100 parts by weight of the positive electrode active material. If the amount of the third particles PTC3 satisfies these ranges, deterioration of the lifespan can be minimized, the stability of the positive electrode active material can be maximized, and the capacity properties can be improved.
[0143] The positive electrode active material of the present disclosure can improve the mixture powder compaction density. In an embodiment, the powder compaction density of the positive electrode active material of the present disclosure can be about 2 g / cc to about 3 g / cc or about 2.5 g / cc to about 2.8 g / cc or about 2.6 g / cc to about 2.8 g / cc.
[0144] The rechargeable lithium battery including the positive electrode active material of the present disclosure can have an excellent average voltage. In an embodiment, the average voltage of the rechargeable lithium battery of the present disclosure can be about 3.2 V to about 4.5 V. For example, the average voltage range can be about 3.5 V to about 3.7 V or about 3.55 V to about 3.65 V.
[0145] The rechargeable lithium battery including the positive electrode active material of the present disclosure can have improved lifespan characteristics. In an embodiment, the rechargeable lithium battery of the present disclosure can have a capacity retention rate of about 95% or more after being charged and discharged at a constant current of about 0.2 C for 50 times at the voltage. For example, the capacity retention rate can be about 97% to about 100% or about 98% to about 100%.
[0146] Hereinafter, embodiments and comparative examples of the present disclosure will be described. However, these embodiments are merely illustrative of the present disclosure, and the present disclosure is not limited to these embodiments.
[0147] Preparation Example 1: Preparation of first particle in single particle form
[0148] FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide were mixed at a molar ratio of Fe:Li:Ti = about 1:1.03:0.004. To the mixture, 10 wt% of glucose was added. The mixture was evaporated and dried by ball milling of the mixture. The dried mixture was baked at about 750°C for about 10 hours under a nitrogen atmosphere. The baked product was ground to obtain first particles in a single particle form. The average size of the first primary particles of the first particles in a single particle form was about 200 nm to about 300 nm.
[0149] Preparation Example 2: Preparation of first particle in secondary particle form
[0150] FePO4 iron phosphate precursor, lithium carbonate, and titanium dioxide were mixed at a molar ratio of Fe:Li:Ti = about 1:1.03:0.004. To the mixture, 10 wt% of glucose was added. The mixture was evaporated and dried by ball milling of the mixture. The dried mixture was baked at about 750°C for about 10 hours under a nitrogen atmosphere. The baked product was ground to obtain first particles in a single particle form. The average size of the first primary particles of the first particles in a single particle form was about 200 nm to about 300 nm.
[0151] Preparation Example 3: Preparation of second particle in secondary particle form
[0152] In 100 ml of distilled water, 0.170 g of MnSO4·H2O and 0.228 g of (NH4)2S2O8 were dissolved, and to this, sulfuric acid was added to adjust the pH to 1, followed by reaction at about 130°C for about 10 hours to obtain a solid precipitate. The precipitate thus obtained was washed with distilled water several times, and dried at about 300°C for about 3 hours to obtain a solid MnO2 having an average particle diameter of about 5 μm.
[0153] Li2CO3 and MnO2 were thus synthesized and mixed so that the molar ratio of Li and Mn became about 1:2, and heated at about 600°C for about 10 hours to synthesize LiMn2O4 particles having an average particle diameter of about 8 μm.
[0154] Preparation Example 4: Preparation of third particle in single particle form
[0155] A high-nickel-based precursor was prepared using a co-precipitation method. In particular, nickel sulfate (NiS04-6H20), cobalt sulfate (CoS04-7H20), and manganese sulfate (MnS04-3H20) having a molar ratio of about 93:5:2 as raw materials of a nickel-based metal hydroxide were dissolved in distilled water as a solvent to prepare a metal raw material mixture. The metal raw material mixture, ammonia water, and sodium hydroxide were put into a reactor and reacted. The slurry solution in the reactor was filtered and rinsed with high-purity distilled water. The rinsed material was dried in a hot air oven at about 210°C for about 24 hours to obtain small-sized precursors (Ni 0.93 Co 0.05 Mn 0.02 (OH)2) powder.
[0156] The high-nickel-based precursor and anhydrous lithium hydroxide (LiOH) were dry-mixed using a Henschel mixer. The mixing was performed so that the molar ratio of lithium and transition metals was about 1:1. As used herein, the transition metal means the sum of transition metals (Ni+Co+Mn) contained in the high-nickel-based precursor. Flux was added to the mixture, and the mixture was heat-treated (i.e., a baking process) at about 750°C for about 15 hours under an oxygen atmosphere to synthesize third particles as a high-nickel-based positive electrode active material. The third particles were milled using a jet mill at a pressure of 3 bar.
[0157] The third particles were added to distilled water and rinsed. Boron oxide and aluminum oxide corresponding to about 3 mol% based on the sum of transition metals of the third particles were added to perform boron and aluminum coating. The third particles were dried at about 150°C for about 12 hours and heated (i.e., surface treatment) at about 700°C for about 15 hours under an oxygen atmosphere.
[0158] Preparation Example 5: Preparation of a main active material
[0159] A main active material was prepared by mixing the first particles of Preparation Example 2 and the second particles of Preparation Example 3 in a weight ratio of about 46:54.
[0160] Preparation Example 6
[0161] A main active material was prepared by mixing the first particles of Preparation Example 2 and the second particles of Preparation Example 3 in a weight ratio of about 55:45.
[0162] Example 1: Preparation of a final positive electrode active material
[0163] A positive electrode active material was prepared by mixing the main active material of Preparation Example 5 and the third particles of Preparation Example 4 in a weight ratio of about 90:10.
[0164] Example 2
[0165] A positive electrode active material was prepared by mixing the main active material of Preparation Example 5 and the third particles of Preparation Example 4 at a weight ratio of about 85:15.
[0166] Example 3
[0167] A positive electrode active material was prepared by mixing the main active material of Preparation Example 5 and the third particles of Preparation Example 4 at a weight ratio of about 80:20.
[0168] Example 4
[0169] A positive electrode active material was prepared by mixing the main active material of Preparation Example 6 and the third particles of Preparation Example 4 at a weight ratio of about 90:10.
[0170] Example 5
[0171] A positive electrode active material was prepared by mixing the main active material of Preparation Example 6 and the third particles of Preparation Example 4 at a weight ratio of about 85:15.
[0172] Example 6
[0173] A positive electrode active material was prepared by mixing the main active material of Preparation Example 6 and the third particles of Preparation Example 4 at a weight ratio of about 80:20.
[0174] Comparative Example 1
[0175] A positive electrode active material was prepared by mixing the main active material of Preparation Example 5 and the third particles of Preparation Example 4 at a weight ratio of about 95:5.
[0176] Comparative Example 2
[0177] A positive electrode active material was prepared by mixing the main active material of Preparation Example 5 and the third particles of Preparation Example 4 at a weight ratio of about 75:25.
[0178] Comparative Example 3
[0179] A positive electrode active material was prepared by mixing the main active material of Preparation Example 5 and the third particles of Preparation Example 4 at a weight ratio of about 70:30.
[0180] Comparative Example 4
[0181] A positive electrode active material was prepared by mixing the main active material of Preparation Example 6 and the third particles of Preparation Example 4 at a weight ratio of about 95:5.
[0182] Comparative Example 5
[0183] A positive electrode active material was prepared by mixing the main active material of Preparation Example 6 and the third particles of Preparation Example 4 at a weight ratio of about 75:25.
[0184] Comparative Example 6
[0185] A positive electrode active material was prepared by mixing the main active material of Preparation Example 6 and the third particles of Preparation Example 4 at a weight ratio of about 70:30.
[0186] Manufacture of positive electrode
[0187] A positive electrode slurry was prepared by mixing 95 wt% of the final positive electrode active material, 3 wt% of a polyvinylidene fluoride binder, and 2 wt% of a carbon black conductive material in an N-methylpyrrolidone solvent. The slurry was coated on an aluminum current collector, dried, and roll-pressed to produce a positive electrode.
[0188] Manufacture of negative electrode
[0189] Graphite, a binder (PVDF), and a conductive material (carbon black) were mixed in an N-methylpyrrolidone solvent at a weight ratio of 95:3:2 to prepare a negative electrode active material slurry. The negative electrode active material slurry was coated on a copper current collector, dried, and roll-pressed to produce a negative electrode.
[0190] Manufacture of rechargeable lithium battery
[0191] A coin half-cell was formed using the prepared positive and negative electrodes. A polypropylene film (Celgard 3510) was used as a separator. The electrolyte used was a mixture of 1.3 M LiPF6 with a solvent mixture of ethylene carbonate (EC), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) in a volume ratio of 2:6:2.
[0192] Evaluation Example 1: Surface analysis of positive electrode active material
[0193] The scanning electron microscope (SEM) images of the first particles prepared in Preparation Example 1 and Preparation Example 2 are shown in FIG. Figures 8A to 8D The SEM image of the second particles prepared in Preparation Example 3 is shown in Figure 9A and Figure 9B The SEM image of the third particle prepared in Preparation Example 4 is shown in Figure 10A and Figure 10B Shown in.
[0194] refer to Figure 8A and Figure 8B , it can be seen that the first particles of Preparation Example 1 according to the present disclosure have the form of fine single particles with nanometer size. Figure 8C and Figure 8D , it can be seen that the first particles of Preparation Example 2 according to the present disclosure have a spherical secondary particle form in which a plurality of first primary particles are aggregated. It can also be seen that compared with the primary particles of Preparation Example 1, the primary particles of Preparation Example 2 have a small particle size and are uniform.
[0195] Referring to Figure 9A and Figure 9B , it can be seen that the second particles have a secondary particle form in which a plurality of second primary particles are aggregated. Referring to Figure 10A and Figure 10B , it can be seen that the third particles are single crystals or have a form in which a plurality of single particles are attached to each other.
[0196] Evaluation Example 2: Evaluation of active material
[0197] The powder packing density (PD) of the positive electrode active materials of Examples 1 to 6 and Comparative Examples 1 to 6 is shown in Table 1. The powder packing density was measured by placing 3 g of the positive electrode active material in a powder packing mold and applying a force of about 4.0 metric tons for about 30 seconds.
[0198] Table 1
[0199]
[0200] Referring to Table 1, it can be seen that the positive electrode active materials according to Examples 1 to 6 have similar powder packing densities compared to the positive electrode active materials of Comparative Examples 1 to 6.
[0201] Evaluation Example 3: Evaluation of battery characteristics
[0202] The properties of rechargeable lithium batteries manufactured using the positive electrode active materials of Examples 1 to 6 and Comparative Examples 1 to 6 were evaluated.
[0203] The rechargeable lithium battery was initially charged under constant current (about 0.2C) and constant voltage (about 4.25V, about 0.01C cutoff) conditions at 25°C, and after resting for about 10 minutes, discharged under constant current (about 0.2C) until about 2.5V to perform initial charge and discharge, to obtain initial charge capacity (4.25V charge amount) and initial discharge capacity (4.25V discharge amount), and efficiency (4.25V life (%)) was expressed as initial charge capacity / initial discharge capacity. Then, 50 times of charge and discharge were performed at about 0.2C (about 4.25V, about 0.01C cutoff) / 0.2C (about 2.5V, about 0.01C cutoff), and life (4.25V life (% after 50 cycles)) was expressed as discharge capacity after the 50th cycle / initial discharge capacity. The average voltage was obtained by integrating the area under the discharge voltage curve (voltage-capacity graph) after initial charge and discharge of the battery cell, and then dividing the integral by the discharge capacity. The evaluation results of the battery properties are shown in Table 2 below. Then, the battery was charged and discharged at a rate of 0.2C / 0.2C in a voltage range of 3.0V~4.45V at 25°C to calculate the energy density. The energy density was obtained by using the following calculation equation: {average driving voltage (V) x capacity (Ah) / battery cell weight (kg)}, in which the capacity was calculated by multiplying the positive electrode weight (g) by the discharge capacity (mAhg).
[0204] Table 2
[0205]
[0206] Referring to Table 2, it can be seen that the positive electrode active material according to Examples 1~6 has similar efficiency, average voltage, and energy density compared to the positive electrode active materials according to Comparative Examples 1~6. In addition, it can be seen that the positive electrode active material according to Examples 1~6 has similar or better life characteristics compared to the positive electrode active materials according to Comparative Examples 1~6. In particular, it can be seen that the positive electrode active materials according to Examples 1~3 exhibit high life characteristics of about 98% or more after 50 cycles.
[0207] In the positive electrode active material according to the present disclosure, the olivine-based first particles and the spinel-based second particles constitute the main active material, and by mixing the layered third particles with the main active material, the capacity and energy density can be improved. The positive electrode active material according to the present disclosure can be inexpensive, and can have high average voltage and energy density.
[0208] Although embodiments of the present disclosure have been described, it is understood that the present disclosure is not limited to these embodiments, but various changes and modifications can be made by those of ordinary skill in the art within the spirit and scope of the present disclosure.
Claims
1. A positive electrode active material comprising: first particles including a compound represented by Chemical Formula 1 and having an olivine structure; second particles including a compound represented by Chemical Formula 2 and having a spinel structure; and third particles including a compound represented by Chemical Formula 3 and having a layered structure, wherein the first particles and the second particles constitute a main active material, wherein the amount of the main active material is 80 parts by weight to 90 parts by weight based on 100 parts by weight of the positive electrode active material, and wherein the amount of the third particles is 10 parts by weight to 20 parts by weight based on 100 parts by weight of the positive electrode active material: wherein Chemical Formula 1 is: wherein 0.8≤a1≤1.2, 0.1≤x1≤1.0, 0.001≤y1≤0.05, 0≤b1≤0.05, x1+y1=1, and B is at least one of Ti, Mg, V, and Nb, Li a1 Fe x1 B y1 PO 4-b1 wherein Chemical Formula 2 is: wherein 0.8≤a2≤1.2, 1.9≤x2≤2.05, 0≤y2≤0.05, and 0≤b2≤0.05, Li a2 Mn x2 Mg y2 O 4-b2 wherein Chemical Formula 3 is: wherein 0.8≤a2≤1.2, 0.9≤x3≤1.0, 0≤y3≤0.1, 0≤z3≤0.1, 0≤b3≤0.05, x3+y3+z3=1, and E is Al and / or Mn. Li a3 Ni x3 Co y3 E z3 O 2-b3 2. The positive electrode active material of claim 1, wherein the amount of Mn is 40 mol% to 70 mol% based on metal elements other than lithium in the main active material.
3. The positive electrode active material of claim 1, wherein the mixed ratio of the first particles and the second particles is 4:6 to 6:4 based on weight.
4. The positive electrode active material of claim 1, wherein the first particles include first primary particles, and the second particles have a secondary particle form in which a plurality of second primary particles are aggregated.
5. The positive electrode active material of claim 4, wherein the average diameter of the first primary particles is smaller than the average diameter of the second primary particles.
6. The positive electrode active material of claim 4, wherein the first particles have a single particle form, the average diameter of the first particles is 0.5 μm to 2.5 μm, and the average diameter of the first primary particles is 200 nm to 300 nm.
7. The positive electrode active material of claim 4, wherein the first primary particles are aggregated with each other, the average diameter of the first particles is 3 μm to 10 μm, and the average diameter of the first primary particles is 100 nm to 200 nm.
8. The positive electrode active material of claim 4, wherein the average diameter of the second primary particles is 0.5 μm to 3 μm.
9. The positive electrode active material of claim 1, wherein the first particles include a coating layer containing a carbon element, and the amount of the carbon element in the first particles is 1.5 wt% to 2.5 wt%.
10. The positive electrode active material of claim 1, wherein the third particles have a single particle form. 11. The positive electrode active material of claim 1, wherein the third particles have a form in which a plurality of single particles are attached to each other, and the average diameter of the first particles is smaller than the average diameter of the third particles.
12. The positive electrode active material of claim 1, wherein the average diameter of the third particles is 2 μm to 5 μm.
13. The positive electrode active material of claim 1, wherein the powder tap density of the positive electrode active material is 2.6 g / cc to 2.8 g / cc.
14. A positive electrode for a rechargeable lithium battery, the positive electrode comprising: a positive electrode current collector; and a positive electrode active material layer on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material of any one of claims 1 to 13, an electrically conductive material, and a binder.
15. The positive electrode for a rechargeable lithium battery of claim 14, wherein the amount of the binder is 0.5 parts by weight to 5 parts by weight, based on 100 parts by weight of the positive electrode active material.
16. The positive electrode for a rechargeable lithium battery of claim 14, wherein the binder comprises at least one of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, an oxirane-containing polymer, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon.
17. The positive electrode for a rechargeable lithium battery of claim 14, wherein the amount of the electrically conductive material is 0.5 parts by weight to 5 parts by weight, based on 100 parts by weight of the positive electrode active material.
18. The positive electrode for a rechargeable lithium battery according to claim 14, wherein said electrically conductive material comprises: a carbon-based material including natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube; a metal-based material including copper, nickel, aluminum, or silver and having a form of a metal powder or a metal fiber; an electrically conductive polymer including a polyphenylene derivative; or a mixture thereof.
19. A rechargeable lithium battery, comprising: the positive electrode of any one of claims 14 to 18; a negative electrode comprising a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector; and a separator between the positive electrode and the negative electrode.
20. The rechargeable lithium battery of claim 19, wherein the energy density of the rechargeable lithium battery is 450 Wh / kg to 550 Wh / kg.
Citation Information
Patent Citations
Base station for aerial network and beamforming method thereof
KR1020240054509A